2005
DOI: 10.1109/led.2005.851822
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer-deposited Si-nitride/SiO/sub 2/ stack gate dielectrics for future high-speed DRAM with enhanced reliability

Abstract: Atomic layer-deposited (ALD) Si-nitride/SiO 2 stack gate dielectrics were applied to high-performance transistors for future scaled DRAMs. The stack gate dielectrics of the peripheral pMOS transistors excellently suppress boron penetration. ALD stack gate dielectrics exhibit only slightly worse negative-bias temperature instability (NBTI) characteristics than pure gate oxide. Enhanced reliability in NBTI was achieved compared with that of plasma-nitrided gate SiO 2. Memory-cell (MC) nMOS transistors with ALD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The flat-band voltages (V fb ) extracted from the high-frequency capacitance-voltage measurement for these three wafers are 1.10, 1.02, and 0.98 V for p-type gate and −1.02, −1.01, and −1.00 V for n-type gate, respectively. The difference in V fb of the p-type gate samples arises from the boron penetration, as the SiON film with higher nitrogen content can suppress the boron penetration more effectively [21]. On the other hand, the similarity in V fb of the n-type gate samples indicates that the nitridation-related positive trapped charge in the bulk oxide is minor or has similar density for our three wafers with different nitrogen contents.…”
Section: Device and Measurement Detailsmentioning
confidence: 86%
“…The flat-band voltages (V fb ) extracted from the high-frequency capacitance-voltage measurement for these three wafers are 1.10, 1.02, and 0.98 V for p-type gate and −1.02, −1.01, and −1.00 V for n-type gate, respectively. The difference in V fb of the p-type gate samples arises from the boron penetration, as the SiON film with higher nitrogen content can suppress the boron penetration more effectively [21]. On the other hand, the similarity in V fb of the n-type gate samples indicates that the nitridation-related positive trapped charge in the bulk oxide is minor or has similar density for our three wafers with different nitrogen contents.…”
Section: Device and Measurement Detailsmentioning
confidence: 86%
“…1 in ref. 5). To further clarify the reason of the V th difference, the V th values of the n þ -and p þ -poly-Si-gated n-and p-MOSFETs in other lot (all the samples have an expected EOT of 2.5 nm) are compared in Fig.…”
Section: Mosfet Fabrication and Measurementmentioning
confidence: 99%
“…The atomic-layerdeposition (ALD) of Si nitride on SiO 2 can provide such a nitrogen distribution. It has been demonstrated that MOSFETs with ALD Si-nitride/SiO 2 stack gate dielectrics exhibit excellent boron suppression 5) and superior reliability characteristics 6) as compared with their counterparts with pure-SiO 2 or plasma-nitrided SiON gate dielectrics. To implement the Si-nitride/SiO 2 stack dielectrics in the next MOSFET technology generation, the effect of the stack gate dielectrics on carrier mobility should be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The negative bias temperature instability ͑NBTI͒ of p-channel metal-oxide-semiconductor field-effect transistors ͑pMOSFETs͒ has become an important reliability concern in modern complementary metal-oxide-semiconductor ͑CMOS͒ technology, especially when the gate-oxide thickness is scaled down to less than 2.0 nm and also nitrogen is introduced into the gate-SiO 2 film in order to suppress the boron penetration and to increase the dielectric constant. 1,2 Considerable efforts have been done for both static ͑Refs. 3-6͒ and dynamic ͑Refs.…”
Section: Introductionmentioning
confidence: 99%